KEBIJAKAN PERMENPAN DAN RB RI NO. 26 TAHUN 2016 TENTANG PENGANGKATAN PNS DALAM JABFUNG MELALUI PENYESUAIAN/INPASSING TERKAIT JABFUNG PUSTAKAWAN - Supriyanto Supriyanto (Ikatan Pustakawan Indonesia, 2017)
Librarian are recognized as legitimate professional (functional position) in the government.That is professionalism with future prospects for those who have certain skills in the field of